Imagining Pathways for Global Cooperation (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-SA 4.0 License. It is free to read, download and share on Elgaronline.com. This book examines the role of imagination in initiating, contesting, and changing the pathways of global cooperation. Building on carefully contextualized empirical cases from diverse policy fields, regions, and historical periods, it highlights the agency of a wide range of actors in reflecting on past and present experiences and imagining future ways of collective problem solving.